2019
DOI: 10.1136/bmjqs-2019-009932
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of clinical decision support to manage acute kidney injury in secondary care: an ethnographic study

Abstract: BackgroundOver the past decade, acute kidney injury (AKI) has become a global priority for improving patient safety and health outcomes. In the UK, a confidential inquiry into AKI led to the publication of clinical guidance and a range of policy initiatives. National patient safety directives have focused on the mandatory establishment of clinical decision support systems (CDSSs) within all acute National Health Service (NHS) trusts to improve the detection, alerting and response to AKI. We studied the organis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…Other QI work has also reported that it can be hard for staff to incorporate new practices into routine work and that it takes sustained effort and encouragement to embed new practices and habits. 7 8 The T&F group helped navigate the obstacles and sustain the new process after the PDSA cycles.…”
Section: Resultsmentioning
confidence: 99%
“…Other QI work has also reported that it can be hard for staff to incorporate new practices into routine work and that it takes sustained effort and encouragement to embed new practices and habits. 7 8 The T&F group helped navigate the obstacles and sustain the new process after the PDSA cycles.…”
Section: Resultsmentioning
confidence: 99%
“…This resonates with findings from an ethnographic study examining the implementation of AKI clinical decision support systems within hospital trusts. 61 Strategies aimed at eradicating under-diagnosis and containing over-diagnosis may help maximise the utility of AKI as a driver of patient safety and reduce unnecessary additional work and downstream noise within the health system. 61 62 The role of AKI nurse specialists to help place AKI alerts in clinical context and then to coordinate safer transitions of care back into the community warrants further examination.…”
Section: Discussionmentioning
confidence: 99%
“… 61 62 The role of AKI nurse specialists to help place AKI alerts in clinical context and then to coordinate safer transitions of care back into the community warrants further examination. 61 …”
Section: Discussionmentioning
confidence: 99%
“…Table 1 summarizes the studies included in the synthetic analysis. All the studies were conducted in the context of developing countries with the majority conducted in the UK (Bailey et al, 2020;Cresswell et al, 2015Cresswell et al, , 2017Lee et al, 2016;Mozaffar et al, 2016a, b) and the USA (Ash et al, 2012(Ash et al, , 2015Joshi et al, 2022;Simon et al, 2013) as the frontrunners in healthcare digitisation leaving the developing countries context under-investigated. All but three studies investigated the adoption of commercial CDSS (Ash et al, 2012;Bailey et al, 2020;Joshi et al, 2022) in hospitals, leaving the home-grown context under-investigated.…”
Section: Synthesis Analysismentioning
confidence: 99%